Simultaneous engineering - Robinson, Adrian (Manufacturing insights, 2003)
This programme explains simultaneous engineering, what it is and how it works, its applications in specific manufacturing situations, future development and trends. It discusses the results of simultaneous engineering in action at the digital pager manufacturing plant of Motorola, at the Battery Assembly Plant of the Delco Remy Division of General Motors, at the NCR Engineering and Manufacturing plant in Cambridge, Ohio and at the Cadillac Motor Car Division of General Motors Corp.